Holistic Tahfidz Education Based on Pesantren: Bibliometric Analysis of the Integration of Memorization and the Formation of Qur'anic Character - Rita Anisaturrizqi; Fitriyatul Hanifiyah; Prima Cristi Crismono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The character crisis among the youth demands the development of a holistic Islamic education model that not only focuses on cognitive aspects but also balances the integration of affective and psychomotor dimensions. The main objective of this study is to explore a holistic tahfidz education model that integrates Islamic character formation. This research employs a qualitative descriptive method, incorporating a literature study approach to empirical scientific publications, supplemented by bibliometric analysis using VOSviewer to map networks of keywords, author collaborations, and citations within the literature corpus under review. The findings from this research indicate that tahfidz pesantren has strengths in shaping Qur'anic personalities through a combination of memorizing the Qur'an, internalizing spiritual values, habituating moral behavior, and the exemplary role of teachers. Excessive emphasis on memorization targets in some tahfidz programs using mechanical repetition methods can reduce space for deep understanding, thus risking the production of hafidz with minimal contextual understanding of the Qur’an and internalization of substantial values. Referring to the results obtained from the data analysis, a reorientation of the tahfidz curriculum is needed that emphasizes the integration of memorization, contemplation, character education, and moral-based evaluation. By integrating the practice of contemplation, moral education, and social involvement based on the Qur'an into the curriculum, the Tahfidz Islamic Boarding School is believed to be able to form a generation that excels academically, spiritually, and socially, and is ready to become agents of social change in modern society.